EUPHEMISMS IN 2019 PRESIDENTIAL ELECTION DEBATES - Hendri Pitrio Putra; Pratomo Widodo (Leksema: Jurnal Bahasa dan Sastra, 2020)
This research aimed at describing the forms and functions of euphemism in the Presidential and Vice-Presidential Debate of the Republic of Indonesia in 2019. This research also explained the form and function of euphemism that was most dominantlyused and whose speech containing most elements of euphemism. The method used in the research was descriptive qualitative method and content analysis approach. The data sources in this research were videos and transcripts of the Presidential and Vice-Presidential Debate in the first and fifth rounds in 2019. The results of this study revealednine forms of euphemism, namely figurative expression, metaphor, flippancy, circumlocutions, clipping, acronym, abbreviation, one for one substitution, borrowing, and hyperbole. The most dominant euphemism form used was one for One Substitution with the total of 164 or 61.4%. Furthermore, the speech that had the most euphemism was Joko Widodo with the total of 113 euphemisms or 42.3%. Finally, this research also showedfour functions of euphemismas a form of positive imaging, criticizing or insinuating opponents, refining speech, and as a tool for diplomacy.